?NEW PEROXO COMPLEXES OF TH (IV), U(VI), MO(VI) AND W(VI) IONS CONTAINING TRIEN AND 1, 10PHENANTHROLINE (Biological Sciences - PJSIR, 1997)
Some novel peroxo complexes of thetype [Th(02)2L], [U(0)(02)2L] and [M(O)(0)2 L] (M= Mo (VI) andW (VI); L= trien or phenanthroiine) have been isolated and characterized by elemental analyses, magnetic measurements and infrared spectral studies and their reactivity has been explored. The experimental data are consistent with octahedral geometry for the thorium complex, nine-foldcoordination forthemolybdenumandtungstencomplexes.Noneofthe complexesoxidisedtriphenylphosphine or triphenylarsine. The u) (0-0) stretch frequency decreased with increasing metal-ion size.